Peran Pelatihan dan Pegembangan MSDM Terhadap Kompetensi Karyawan - Faida, Rifda; Gala, Reski; Nur, Karyati; Kasmin, Fitriani; Ahmad, Syafar (Annusfy : Journal of Multidisciplinary Research, 2025)
This study aims to analyze the role of human resource (HR) training and development in enhancing employee competence through a literature review. A qualitative method with a literature study approach was employed using 12 articles published between 2020 and 2025. The findings indicate that training plays a crucial role in strengthening employees’ technical skills by reducing competency gaps and improving work effectiveness through needs-based programs. Meanwhile, HR development contributes to long-term competency building, including soft skills such as leadership, communication, creativity, and adaptability. The integration of training and development also fosters a learning culture, increases motivation, enhances loyalty, and improves overall employee performance. Therefore, training and development serve as strategic investments for organizations to develop competent, adaptive, and future-ready human resources